THE PLIOCENE AND PLEISTOCENE SMALL MAMMALS OF EASTERN TRANSBAIKALIA - Erbajeva M.A.; Alexeeva N.V.; Khenzykhenova F.I. (My University, 2001)
The paper deals with the Pliocene and Pleistocene mammalian faunas of Eastern Transbaikalia discovered during the last decade. For the first time for this region four successive small mammalian faunas are recognized. The oldest one is Middle Pliocene and the analogue of the West Transbaikalian Chikoi faunistic complex. The Middle and Late Pleistocene faunas are the analogues of the Tologoi and Upper Paleolithic Faunistic complexes of West Transbaikalia. The Early Pleistocene faunal assemblage represents a new stage (Ustoborian) based on the small mammalian succession in this region.
Keywords: Pleistocene; Pliocene; mammals; Transbaikalia; Кайнозой::Неоген::Плиоцен; Cenozoic::Quaternary::Pleistocene; Cenozoic::Neogene::Pliocene; Кайнозой::Четвертичная::Плейстоцен